Biophysical assessment a comparative study of the Bolusao and Poblacion rivers in Lawaan, Eastern Samar, Philippines. - Gacura, John Rey L. (John Rey L. Gacura, 2018)
The municipality of Lawaan, located in the province of Eastern Samar, has seven river systems stretching up to 500 km. The two major river systems are the Poblacion River, located within the town proper, and the Bolusao River along Barangay Bolusao. This study aims to assess the biophysical components of Bolusao and Poblacion Rivers in Lawaan, Eastern Samar, Philippines. Fish and macroinvertebrate samples were collected from October to November 2017 and January to February 2018. Physico-chemical parameters were not significantly different for all streams in the two rivers, except for the temperature. The most abundant species in Poblacion River was Eubleekeria jonesi (Leiognathidae) and Ambassis interrupta (Ambassidae) in Bolusao River. Chelonodon patoca was the only species known to be widely distributed in the upstream, midstream, and downstream region. Both rivers recorded a high diversity and evenness of fish. Class Malacostraca (39%) was most abundant in Poblacion River while Class Gastropoda (62%) was most abundant in Bolusao River. Macrobrachium rosebergii was found to be widely distributed in all streams of Bolusao River while Neritina turrita was found to be present in both upstream and midstream of Poblacion River. Bolusao River revealed a high diversity for macroinvertebrates while diversity for Poblacion River was low. Species similarity index for both fish and macroinvertebrates was low at 0.39, indicating that the two rivers have distinct species. This study provides an essential baseline information for future monitoring and further conservation strategies for the two rivers.